Old wicked songs - Marans, Jon (Fireside Theatre, 1996)
This play tells the story of Stephen Hoffman, an American piano prodigy desperate to regain his waning creative spark. He travels to Vienna, where he studies under the forced tutelage of an old and eccentric vocal professor. The two could not be more different - one is European, the other American; one passionate; the other technical; and one an anti-Semite and the other, a Jew. What follows is a game of trading challenges, tirades, and insults revealing both the sinister and the noble sides of each man.